A Nutrition Behavior Change Program Moderately Improves Minimum Diet Diversity and Handwashing Behaviors Among Tea Workers in Assam and Tamil Nadu, India. Issue 2 (June 2022) - Nyhus Dhillon, Christina; Vossenaar, Marieke; Weiligmann, Bärbel; Sanwal, Neha; Djimeu, Eric W.; Kneepkens, Mirjam; Mushahary, Biju; Stone, Genevieve; Neufeld, Lynnette M.
Many workers in global supply chains remain nutritionally vulnerable despite the income they earn. The Seeds of Prosperity (SOP) program was implemented in Tamil Nadu and Assam, India, for tea supply chain workers (estate workers, small holder farmers, and farm workers). The aim was to enhance demand for diverse and nutritious foods and improve practices related to handwashing. The program used a behavior change communication approach wherein participants received weekly 1-hour group sessions with messaging on dietary diversity for 5 weeks and handwashing for 4 weeks. An impact evaluation was conducted to estimate changes in reported dietary and hygiene knowledge and behaviors among women. The study used a longitudinal quasi-experimental design in a subsample of program participants at baseline and post-intervention among both intervention and comparison. There was a small but significant increase in mean dietary diversity (DD) for all 4 worker groups (ranging from DD score changes of 0.3 to 0.7; P < .05) and in the proportion of women meeting the minimum dietary diversity in 2 of the 4 groups. Similarly, a significant increase in the mean number of handwashing moments was observed in 2 of the worker groups. An increase in home garden use was observed in 1 of the 4 worker groups. While the SOP program resulted in improvements in dietary diversity, most tea farming women still do not achieve minimum dietary diversity. Nutritious food access may be an important constraint to further improvement.